Disgust-Related Olfactory Processing: The Role of Gender and Trait Disgust. (March 2017) - Schienle, Anne; Schöpf, Veronika
For the rejection of disgusting and potentially health-threatening food, the sense of smell plays a critical role. We conducted two experiments in order to investigate the role of gender and trait disgust (the temporally stable tendency to experience disgust across different situations) on disgust-related olfactory processing. A total of 40 men and women (Study 1), as well as a group of women divided according to high versus low trait disgust (Study 2, n = 59), were compared with regard to their odor thresholds for carbon disulfide (which smells like spoiled food) and a control stimulus ( n -butanol). The stimuli were rated for experienced arousal, negative valence, and familiarity. In addition, all participants underwent the "Sniffin' Sticks" battery assessing general olfactory performance. We found that women had a lower carbon disulfide threshold and rated this odorant as more unpleasant than men. Trait disgust was neither associated with the detection of the odorant signaling spoilage, nor with general olfactory function. The latter finding questions the role of this personality trait for olfactory-driven food-rejection responses, at least for normosmic individuals.